RNA architecture influences plant biology - Zhu, Jiaying (J Exp Bot, 2021)
The majority of the genome is transcribed to RNA in living organisms. RNA transcripts can form astonishing arrays of secondary and tertiary structures via Watson–Crick, Hoogsteen, or wobble base pairing. In vivo, RNA folding is not a simple thermodynamic event of minimizing free energy. Instead, the process is constrained by transcription, RNA-binding proteins, steric factors, and the microenvironment. RNA secondary structure (RSS) plays myriad roles in numerous biological processes, such as RNA processing, stability, transportation, and translation in prokaryotes and eukaryotes. Emerging evidence has also implicated RSS in RNA trafficking, liquid–liquid phase separation, and plant responses to environmental variations such as temperature and salinity. At molecular level, RSS is correlated with splicing, polyadenylation, protein synthesis, and miRNA biogenesis and functions. In this review, we summarize newly reported methods for probing RSS in vivo and functions and mechanisms of RSS in plant physiology.